The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1037/1099-9809.12.4.658
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and exiting homelessness among homeless adolescents.

Abstract: This paper examines how newly homeless adolescents' discrimination experiences were associated with exiting homelessness after six months. A sample of 262 homeless adolescents, aged 12 to 20 years, were recruited and followed longitudinally (six-month retention rate = 88%). Discrimination was related to being gay, lesbian, or bisexual (LGB). Discrimination from family was related to exiting homelessness. Other than those who were LGB, adolescents who reported discrimination from their families were more likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 55 publications
2
30
0
2
Order By: Relevance
“…Those youth who reported leaving home because they were kicked out or removed by authorities as opposed to making the choice to leave were more likely to follow a ST rather than a LT inconsistently housed trajectory. This is consistent with the findings that homeless adolescents who report that their families discriminate against them (i.e., hassle, abuse, or assault because homeless, lesbian/gay/bisexual, or because of race) also exit homelessness more quickly [36]. Youth who did not choose to leave home but find themselves unsheltered because of rejection or other mistreatment by their family may be more willing to accept help leading to stable housing or more willing to actively seek housing.…”
Section: Discussionsupporting
confidence: 90%
“…Those youth who reported leaving home because they were kicked out or removed by authorities as opposed to making the choice to leave were more likely to follow a ST rather than a LT inconsistently housed trajectory. This is consistent with the findings that homeless adolescents who report that their families discriminate against them (i.e., hassle, abuse, or assault because homeless, lesbian/gay/bisexual, or because of race) also exit homelessness more quickly [36]. Youth who did not choose to leave home but find themselves unsheltered because of rejection or other mistreatment by their family may be more willing to accept help leading to stable housing or more willing to actively seek housing.…”
Section: Discussionsupporting
confidence: 90%
“…32 Reviews of prior research have documented links between verbal and physical harassment from family and peers, running away and experience homelessness, and elevated substance use and depression among sexual minority youth who have experiencing homelessness. 16,33,34 Findings from a representative sample of high school students point to rejection and discrimination within the family due to sexual orientation as a likely cause of homeless disparities experienced by sexual minority youth compared to heterosexual youth, but little research has assessed possible causal factors of these disparities. 15 Although experiencing homelessness as an outcome of discrimination and marginalization has been documented among samples of sexual minority youth, research that that empirically examines the effects of minority stress on developmental pathways associated with homelessness and health of YMSM has been limited.…”
mentioning
confidence: 99%
“…It logically follows then*and is supported by the literature *that homeless sexual minority youths face double jeopardy, first from their status as homeless adolescents and second, from their status as gay, lesbian, bisexual, or transgender young people. By comparing the experiences of homeless sexual minority youths with those of homeless heterosexual youths, numerous studies have demonstrated this increased risk (Cochran et al 2002;Hebl et al 2002;Milburn et al 2006;Ryan 2001). Findings from studies such as these are helpful to service providers who offer programs for homeless youths, as well as to providers who serve youths and young adults who are at risk for homelessness.…”
Section: Introductionmentioning
confidence: 98%